Radiographic and CT Assessment of Reduction of Calcaneus Fractures Using a Limited Sinus Tarsi Incision. (September 2016) - Scott, Aaron T.; Pacholke, David A.; Hamid, Kamran S.
Background: The lateral extensile incision for fixation of displaced intra-articular calcaneus fractures allows for fracture reduction but has been associated with high rates of soft tissue complications. This has prompted a search for less invasive methods of fracture fixation. The purpose of the present study was to determine the adequacy of reduction and rate of complications associated with operative fixation of calcaneal fractures using a limited sinus tarsi approach. Methods: A limited sinus tarsi incision with plate fixation was utilized for treatment of 39 displaced intra-articular calcaneal fractures in 35 consecutive patients as part of a single surgeon series. Imaging assessment of previously described fracture displacement measures was undertaken in preoperative and postoperative radiographs and CT. A retrospective chart review was conducted to identify postoperative complications. Results: Mean preoperative Bohler angle measurement was 7.7 (range, –26.0 to 30.0) degrees and the mean final postoperative standing Bohler angle was 25.5 (range, 12.3 to 37.7) degrees. Postoperative CT demonstrated that subtalar articular reduction was within 2 mm of anatomic in 91% of patients. There were 2 instances of superficial wound dehiscence (5.1%) and 1 deep infection (2.6%) that required debridement and complete hardware removal. Visual analog score (VAS) for pain averaged 3 of 10 in the 32 available patients at 1-year follow-up. Eight of these patients (25%) reported no pain (0/10) at final follow-up. Conclusion: Operative fixation of displaced intra-articular calcaneal fractures utilizing the limited sinus tarsi approach resulted in acceptable fracture reduction and a low rate of complications. Level of Evidence: Level IV, retrospective case series.